PENGARUH PROFESIONALISME PEMERIKSA PAJAK, KEPUASAN KERJA, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Kindi Avianda (Media Riset Akuntansi, Auditing & Informasi, 2014)
This research aimed to test the influence of job satisfaction, commitment organization and motivation on work performance employees for professional tax inspector. Data in research is done through distribute a questionnaire to examiner tax in East Jakarta namely KPP-Pratama Jakarta Pasar Rebo, Kpp-Pratama Jakarta Kramat Jati, Kpp-Pratama Jakarta Jatinegara, KPP-Pratama Jakarta Duren Sawit, Kpp-Pratama Jakarta Matraman, Kpp-Pratama Jakarta Pulogadung, Kpp-Pratama Jakarta Cakung 1, Kpp-Pratama Jakarta Cakung 2. The number of respondents sample are 72. The results show that work motivation significantly influence on performance. The other side, professionalism, job satisfaction and commitment do not influence performance.